In Situ Measuring of Relative Dielectric Permittivity to Calculate Electromagnetic Wave Velocity - Thabit, Jassim M.; Bakir, Hawkar B. (Iraqi Journal of Science, 2022)
The relative dielectric permittivity (dielectric constant) values for various materials are measured on site. The calculated values that are derived from measuring the ratio of the electrical capacitance of a cell when the sample of the material is placed. Parallel plate technique that consists of two parallel circular metallic plates is used. The instrument made up of aluminum which acts as electrodes and stuffed inside the PVC cylinder. Then the thin sheet of material (models) sandwiched between the two plates. Calculation of dielectric constant (εr) through this new technique gives a new velocity value of electromagnetic wave that propagates underground. These measured velocity values will utilize in Ground Penetration Radar (GPR) data acquisition and interpretation in order to increase the resolution of the obtained radargrams.